Share of Mass Transit Miles Traveled and Reduced Motor Vehicle Fatalities in Major Cities of the United States - Stimpson, Jim P. (J Urban Health, 2014)
The USA leads the developed world in motor vehicle fatalities, presenting a critical public health threat. We examined whether an increasing share of mass transit use, relative to vehicle miles traveled on public roads, was associated with reduced motor vehicle fatalities. We used annual city-level data for the USA from 1982–2010 provided by the Fatality Accident Reporting System, the Texas A&M Transportation Institute, the Census Bureau, and the National Oceanic and Atmospheric Administration to estimate a structural equation model of the factors associated with mass transit miles and motor vehicle fatalities. The final analytic data included 2,900 observations from 100 cities over 29 years. After accounting for climate, year, and the economic costs of driving, an increasing share of mass transit miles traveled per capita was associated with reduced motor vehicle fatalities. The costs of congestion to the average commuter and gas prices were positively associated with increasing the share of mass transit miles traveled. The economic costs of driving increased over time, while both the fatality rate and the share of mass transit miles traveled decreased over time. Increasing the share of mass transit miles traveled may be associated with fewer motor vehicle miles traveled. Increasing mass transit uptake may be an effective public health intervention to reduce motor vehicle fatalities in cities.